The Eudaimonist Ethics of al-Fārābī and Avicenna - Mattila, Janne (Brill, 2022)
Al-Fārābī and Avicenna are the two most influential authors of the classical period of Arabic philosophy, yet their ethical thought has been largely overlooked by scholars. In this book, Janne Mattila provides the first comprehensive account of the ethics of these important philosophers. The book argues that even if neither of them wrote a major ethical work, their ethical writings form a coherent ethical system, especially when understood in the context of philosophical psychology, cosmology, and metaphysics. The resulting ethical theory is, moreover, not derivative of their classical predecessors in any simple way. The book will appeal to those with interest in Arabic/Islamic philosophy, Islamic intellectual history, classical philosophy, and the history of moral philosophy.